Relationship between childhood adversity and bipolar affective disorder: systematic review and meta-analysis. (December 2016) - Palmier-Claus, J. E.; Berry, K.; Bucci, S.; Mansell, W.; Varese, F.
Abstract : Background: The relationship between childhood adversity and bipolar affective disorder remains unclear. Aims: To understand the size and significance of this effect through a statistical synthesis of reported research. Method: Search terms relating to childhood adversity and bipolar disorder were entered into Medline, EMBASE, PsycINFO and Web of Science. Eligible studies included a sample diagnosed with bipolar disorder, a comparison sample and a quantitative measure of childhood adversity. Results: In 19 eligible studies childhood adversity was 2.63 times (95% CI 2.00–3.47) more likely to have occurred in bipolar disorder compared with non-clinical controls. The effect of emotional abuse was particularly robust (OR = 4.04, 95% CI 3.12–5.22), but rates of adversity were similar to those in psychiatric controls. Conclusions: Childhood adversity is associated with bipolar disorder, which has implications for the treatment of this clinical group. Further prospective research could clarify temporal causality and explanatory mechanisms.